2018
DOI: 10.4172/2167-0420.1000418
|View full text |Cite
|
Sign up to set email alerts
|

Age, Anthropometric Measurements and Mode of Delivery among Primigravidae Women at Addis Ababa Governmental Hospitals, Ethiopia

Abstract: Background: In developing countries, a significant number of maternal deaths are attributable to the complications of obstructed labor. Identifying women at risk for Cephalopelvic Disproportion (CPD) prepares physicians for on time treatment and enables them to minimize maternal-fetal trauma that accompanies this midwifery emergency. The study aims to identify diagnostic accuracy of maternal age and anthropometric measurements to predict CPD among Primigravidae women visiting Addis Ababa Governmental Hospital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Similar to study conducted by Demitew S et al in which foot length 22.6 ± 0.7 cm underwent LSCS for CPD and foot length 23.7 ± 0.9 cm delivered vaginally. 5 and Deepika N et al in which foot length 24.1 ± 0.1 cm underwent LSCS for CPD and foot length 25.3 ± 1.9 cm delivered vaginally 6 , another similar study Santosh J et al in which foot length 22.3 ± 1.1 cm underwent LSCS for CPD and foot length 23.2 ± 1.9 cm delivered vaginally. 7 But contrary to the studies conducted by Awonuga et al 8 and Mahmood et al, 9 no significant correlation was found (Have taken Foot Length < 18 cm and > 18 cm).…”
Section: Discussionmentioning
confidence: 93%
“…Similar to study conducted by Demitew S et al in which foot length 22.6 ± 0.7 cm underwent LSCS for CPD and foot length 23.7 ± 0.9 cm delivered vaginally. 5 and Deepika N et al in which foot length 24.1 ± 0.1 cm underwent LSCS for CPD and foot length 25.3 ± 1.9 cm delivered vaginally 6 , another similar study Santosh J et al in which foot length 22.3 ± 1.1 cm underwent LSCS for CPD and foot length 23.2 ± 1.9 cm delivered vaginally. 7 But contrary to the studies conducted by Awonuga et al 8 and Mahmood et al, 9 no significant correlation was found (Have taken Foot Length < 18 cm and > 18 cm).…”
Section: Discussionmentioning
confidence: 93%
“…Foot length is measured by a wooden centimeter from the heel to the tip of the longest toe. All maternal anthropometric measurements were taken three times, and the average was taken (17). Maternal hemoglobin (Hgb) was determined using a portable hemoglobinometer, the HemoCue Hgb analyzer (HemoCue Hb 201+, Sweden), by taking a drop of blood and puncturing the tip of the middle finger of the mother with a sterile lancet.…”
Section: Methodsmentioning
confidence: 99%
“…Height: Measured in the standing position following standards of measuring height by using a stadiometer (mothers stood next to a wall with their feet and knees together, knees straight, heels, legs, hip, shoulders, back of the head parallel to the wall, their body completely flat and stretched, hands hanging on both sides, and looking straight ahead and standing height was measured in centimeter (cm) (17).…”
Section: Operational Definitions and Definition Of Termsmentioning
confidence: 99%
“…Michaelis noted the difference in size or shape of this area in women with and without contracted pelvis and also explained its importance for the pelvic cavity [6,7]. Maternal height is presently the only parameter included in ANC charts for the identification of women at risk of pelvic disproportion [4,[8][9][10]. Other factors such as external pelvic diameters, foot length, symphysio fundal height, weight gain during pregnancy have been evaluated in various studies [4,[8][9][10] with controversial results in some of them [4,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal height is presently the only parameter included in ANC charts for the identification of women at risk of pelvic disproportion [4,[8][9][10]. Other factors such as external pelvic diameters, foot length, symphysio fundal height, weight gain during pregnancy have been evaluated in various studies [4,[8][9][10] with controversial results in some of them [4,8,10]. The present study aims to assess the validity of sacral rhomboid diameters along with maternal height in primigravida at term pregnancy to predict the contracted pelvis antenatally.…”
Section: Introductionmentioning
confidence: 99%